Terrain Awareness Using a Tracked Skid-Steering Vehicle With Passive Independent Suspensions - Galati, Rocco; Reina, Giulio (Frontiers in Robotics and AI, 2019)
In this paper, a novel approach for terrain characterization is presented using a tracked skid-steer vehicle with a passive independent suspensions system. a set of physics-based parameters is used to characterize the terrain properties: drive motor electrical currents, the equivalent track, the power spectral density for the vertical accelerations and motor currents. Based on this feature set, the system predicts the type of terrain that the robot traverses. Experimental results obtained on various surfaces are provided to validate the study in the field, showing its potential for application in autonomous robots.